CORRELATION OF DOPPLER WAVEFORM ABNORMALITIES OF HEPATIC VEINS WITH HISTOLOGICAL FINDINGS IN CHRONIC LIVER DISEASE (HCV INFECTION): Correlation of Doppler Waveform Abnormalities - Javed, Koukab; Azam, Malik Nadeem; Akram, Muhammad Hamid (Pakistan Armed Forces Medical Journal, 2008)
Objective: To study the relationship of the abnormalities in Doppler waveform of hepatic veins with histologic findings in chronic liver disease (HCV infection). Design: cross- sectional study. Place and duration of study: Radiology Department Military Hospital Rawalpindi. The duration of study was one year from February 2004 to February 2005. Patients and methods: 50 patients with non de-compensated HCV infection were studied, who were subjected to biopsy by medical specialists. Their Doppler waveforms of hepatic veins were noted. Results: On histopathology, 4 cases (8%) had no evidence of fibrosis, 27 cases (54%) had mild, 15 cases (30%) had moderate and 4 cases (8%) had severe fibrosis. Three patterns of waveform were observed. These waveforms include normal triphasic waveform (type O), decreased amplitude of phasic oscillations without the reversed flow phase (type 1) and completely flat waveform (type 2). Among 33 cases of type 0 flow, majority (85%) had either mild fibrosis. Twelve cases that had type 1 flow, majority (92%) had mild to moderate fibrosis. Out of 5 cases that were observed ultrasound type 2 flow, all had either moderate or severe fibrosis. The degree of fibrosis was related directly to the hepatic vein waveforms abnormalities (p<0.001). Conclusion: Ultrasonographic abnormalities of Doppler waveforms of hepatic veins are equivalent to histology in predicting the progression of CLD.